Phytochemical Analysis, Antioxidant Activity, Fatty Acids Composition, and Functional Group Analysis of Heliotropium bacciferum - Sohail Ahmad; Shabir Ahmad; Ahtaram Bibi; Muhammad Saqib Ishaq; Muhammad Siddique Afridi; Farina Kanwal; Muhammad Zakir; Farid Fatima (The Scientific World Journal)
Heliotropium bacciferum is paramount in medicinal perspective and belongs to Boraginaceae family. The crude and numerous fractions of leaves, stem, and roots of the plant were investigated for phytochemical analysis and DPPH radical scavenging activity. Phytochemical analysis of crude and fractions of the plant revealed the presence of alkaloids, saponins, tannins, steroids, terpenoids, flavonoids, glycosides, and phenols. The antioxidant (free radical scavenging) activity of various extracts of the Heliotropium bacciferum was resolute against 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical with the avail of UV spectrophotometer at 517 nm. The stock solution (1000 mg/mL) and then several dilutions (50, 100, 150, 200, and 250 mg/mL) of the crude and fractions were prepared. Ascorbic acid was used as a standard. The plant leaves (52.59 ± 0.84 to 90.74 ± 1.00), stem (50.19 ± 0.92 to 89.42 ± 1.10), and roots extracts (49.19 ± 0.52 to 90.01 ± 1.02) divulged magnificent antioxidant activities. For the ascertainment of the fatty acid constituents a gas chromatograph hyphenated to mass spectrometer was used. The essential fatty acids for growth maintenance such as linoleic acid (65.70%), eicosadienoic acid (15.12%), oleic acid (8.72%), and palmitic acid (8.14%) were found in high percentage. The infrared spectra of all extracts of the plant were recorded by IR Prestige-21 FTIR model.